Association between ambient particulate matter concentrations and hospitalization for ischemic heart disease (I20-I25, ICD-10) in China: A multicity case-crossover study. (August 2018) - Dai, Xiaotong; Liu, Hui; Chen, Dafang; Zhang, Jun
Abstract: Background: Ischemic heart disease is a serious cause of death. Ambient particulate matter pollution is similarly defined a national environmental issue in China. The objective of this study was to examine the association of particulate matter with hospital admissions for ischemic heart disease in 26 large Chinese cities. Methods: The study identified 720, 261 hospital admissions for ischemic heart disease by using electronic hospitalization summary reports from 1 January 2014 through 31 December 2015. Conditional logistic regression was used to estimate the percent changes with 95% confidence intervals (CIs) in ischemic heart disease admissions in relation to an interquartile range increase in ambient particulate matter concentrations. We also assessed the effect modification of ischemic heart disease risk by geographical region, gender, and age. Results: The means of air pollutants were 63.5 ± 50.6 μg/m 3 for PM2.5, 106.8 ± 71.9 μg/m 3 for PM10 . The levels of PM2.5 and PM10 concentrations in northern China were much higher than those in southern China. Both PM2.5 and PM10 had the strongest effect for daily ischemic heart disease admissions on lag 2 days, with an interquartile range (IQR) increase in PM2.5 (47.5 μg/m 3 ) and PM10 (76.9 μg/m 3 ) at lag 2 days corresponded to a 1.7% (95% CI, 1.5–1.9%) and 2.0% (95% CI, 1.7–2.3%) increase in ischemic heart disease admissions, respectively. Associations with both PM2.5 and PM10 were stronger in northern China than in southern China in all lag structures. In northern China, an IQR increase in PM2.5 and PM10 concentrations at lag 2 days was associated with a 1.8% (95% CI, 1.6–2.1%) and 2.1% (95% CI, 1.8–2.4%) increase in ischemic heart disease admissions, respectively. In southern China, negative associations were observed with PM2.5 and with PM10 almost at all lag structures. Conclusion: Short-term elevations in the levels of PM2.5 and PM10 demonstrate significant associations with an increase in ischemic heart disease. In northern China, the associations between the increase of PM2.5 and PM10 concentrations and IHD admissions were positive. In southern China, the associations were null or negative. Highlights: The association of particulate matter with hospital admissions for ischemic heart disease in China is established. Short-term elevations in PM2.5 and PM10 demonstrate significant associations with increased risk of ischemic heart disease. In northern China, the associations between the increase of PM2.5 and PM10 concentrations and IHD admissions were positive. In southern China, the associations were null or negative.